Plant-specific mitochondrial fission machinery connects mitochondrial dynamics and mitophagosome formation for piecemeal mitophagy - Juncai Ma; Chaorui Li; Kaike Ren; Kaiyan Zhang; Lanlan Feng; Kai Ching Law; Ka Kit Chung; Yizhou Bing; Caiji Gao; Byung-Ho Kang; Xiaohong Zhuang (Proceedings of the National Academy of Sciences, 2025)
As the energy center of the cell, mitochondria display enormous metabolic plasticity to meet the cellular demand for plant growth and development, which is tightly linked to their structural and dynamic plasticity. Mitochondrial number and morphology are coordinated through the actions of the mitochondrial division and fusion. Meanwhile, damaged mitochondrial contents are removed to avoid excess toxicity to the plant cells. Mitophagy, a selective degradation pathway of mitochondria through a double-membrane sac named autophagosome (also known as mitophagosome), plays a crucial role in maintaining mitochondrial homeostasis. Typically, wholesale mitophagy requires the elongation of a cup-shaped phagophore along the entire mitochondrion, which finally seals and closes as a mitophagosome. How plant mitophagosome formation and mitochondria sequestration are coordinated remains incompletely understood. In this work, we report an unappreciated role of the plant-specific mitochondrial fission regulator ELM1, together with the dynamin-related protein family DRP3 and the autophagic regulator SH3P2, to coordinate mitochondria segregation for piecemeal mitophagy under heat stress conditions. Dysfunction in mitochondrial fission activity impairs heat-induced mitophagy, leading to an accumulation of interconnected megamitochondria which are partially sequestered by the ATG8-positive phagophore. Furthermore, we show that the ELM1-mediated piecemeal mitophagy also engages the plant archetypal selective autophagic receptor NBR1. Using 3D tomography analysis, we illustrate the morphological features and spatial relationship of the megamitochondria and phagophore intermediates in connection with the mitochondrial fission sites. Collectively, our study provides an updated model of mitophagosome formation for piecemeal mitophagy mediated by the plant-unique mitochondrial fission machinery.